THE ROLE OF INTERACTIVE LEARNING IN ENHANCING ENGLISH LANGUAGE SKILLS AMONG SECONDARY SCHOOL STUDENTS - Gulzodakhon Qodirova, (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Abstract: Interactive learning has emerged as an effective approach in modern education, promoting student engagement, critical thinking, and communication skills. This study explores the impact of interactive learning techniques on the development of English language skills among secondary school students. The research focuses on methods such as group discussions, role-plays, multimedia-assisted instruction, and collaborative projects to enhance reading, writing, speaking, and listening abilities. Through classroom observations, teacher interviews, and student surveys, the study identifies the advantages and challenges of implementing interactive learning in English language teaching. The findings suggest that students participating in interactive learning activities demonstrate higher motivation, improved language proficiency, and better retention of knowledge compared to traditional teaching methods. Additionally, interactive learning encourages peer collaboration, fosters creativity, and helps learners develop practical communication skills essential for real-life situations. This study highlights the importance of incorporating interactive strategies in the English language curriculum and provides practical recommendations for educators to optimize language learning outcomes.